(x+3)2+2x+2x=24

Simple and best practice solution for (x+3)2+2x+2x=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)2+2x+2x=24 equation:


Simplifying
(x + 3) * 2 + 2x + 2x = 24

Reorder the terms:
(3 + x) * 2 + 2x + 2x = 24

Reorder the terms for easier multiplication:
2(3 + x) + 2x + 2x = 24
(3 * 2 + x * 2) + 2x + 2x = 24
(6 + 2x) + 2x + 2x = 24

Combine like terms: 2x + 2x = 4x
6 + 4x + 2x = 24

Combine like terms: 4x + 2x = 6x
6 + 6x = 24

Solving
6 + 6x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6x = 24 + -6

Combine like terms: 6 + -6 = 0
0 + 6x = 24 + -6
6x = 24 + -6

Combine like terms: 24 + -6 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| Ax+7-7x-a= | | (9x+2)+(178-9x)=180 | | (9x+2)+(178-9x)-180=0 | | 3(2a-7-a)= | | 24-7x=3y | | 30y+1.20y= | | 20sinx-20cosx=0 | | 160=4x^2+156x | | 6w+15= | | 5a-9=-59 | | X+y+x^2+y^2=40 | | X^3+3x^2+2x=40(x+(x+1)+(x+2)) | | 6(5x-12)=18 | | 3g/g | | y+27=56 | | 53+2x=8x-37 | | (x^3)-(2.25x^2)=-1 | | x^3-2.25x^2=-1 | | (4*8*11)-(8*8)= | | 5x+6y-7=0 | | 2x^2-36=12 | | 3*9/22 | | 10/14*100= | | X-22=Y | | 22-5x=7x+10 | | (x^2+1)*2.25=x^2+1+2.25 | | 6y-4y=-8+2 | | 6b-5a=4 | | f(x)=-3x^2+2x+4 | | 7p+2q=-5 | | 4xln(x)=0 | | 2t+11=34 |

Equations solver categories